Cooperative communication system based on convolutional code CDMA techniques - Fadhil M.; Ismail M.; Saif A.; Othman N.S.; Khaleel M. (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper presents the performance of a cooperative communication scheme when communicating over Rayleigh channel. More explicitly, the performances of the Code Division Multiple Access CDMA cooperative schemes with two and eight users, employing systematic convolutional code (CC) are presented. The single relay cooperative network with decodeand- forward (DAF) relay is investigated in the proposed system. The proposed CDMA cooperative scheme is capable of attaining over 2 dB of SNR gain at a Bit Error Rate (BER) of 10-4 in comparison with the non cooperative scheme. The result shows at BER of 10-4the system that employs the Maximum Ratio Combiner (MRC) outperformance the system that employs Equal Gain Combiner (EGC) by about 1.5 dB in terms of SNR. On the other hand, the signal power in cooperative system employing EGC varied from 5 to -20 dB. However, in non cooperative system the signal power varied from -10 to -30 dB. Which approve, those independent copies of the signal received by the receiver lead to mitigate the effect of fading. © 2014 IEEE.